1985
DOI: 10.1111/j.1365-2133.1985.tb02047.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous amyloidosis

Abstract: A patient with a 12-year history of a relapsing bullous dermatosis is presented. Unusual clinical features included urticarial erythema, conspicuous mottled hyper- and depigmentation, lichenification and ichthyosiform hyperkeratosis. Serum immunoglobulin E levels were elevated. Histological examination showing deposits of amyloid in the uppermost dermis confirmed the diagnosis of bullous amyloidosis. Ultrastructurally, blister formation occurred at the level of the lamina lucida. The amyloid did not react with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Among them, alopecia, 109-111 cutis laxa, [112][113][114][115] or bullae. [116][117][118][119][120][121][122][123][124] Blisters are also frequent due to cleavage developing within the amyloid deposits and many times are hemorrhagic and occur on the tongue or bucal mucosa (Fig. 7).…”
Section: Changes In the Skin In Systemic Amyloidosismentioning
confidence: 99%
“…Among them, alopecia, 109-111 cutis laxa, [112][113][114][115] or bullae. [116][117][118][119][120][121][122][123][124] Blisters are also frequent due to cleavage developing within the amyloid deposits and many times are hemorrhagic and occur on the tongue or bucal mucosa (Fig. 7).…”
Section: Changes In the Skin In Systemic Amyloidosismentioning
confidence: 99%
“…Flow cytometry of an aspirated bone marrow specimen yielded a monoclonal population of CD138 positive, IgG κ plasma myeloma cells. Conventional cytogenetic examination showed a normal female karyotype of 46 XX; however, FISH was positive for monosomy of chromosome 13 (loss of both RB1 and LAMP1) in 10.3% of cells, and t [6,7], indicating overexpression of BCL1, and cyclin D1 (CCND1/IGH) rearrangement in 5.8% of the cells. Bone survey revealed multiple lytic bone lesions, including the left greater femoral trochanter, right humeral head, and T12 vertebral bodies.…”
Section: Case Reportmentioning
confidence: 99%
“…5,7 Occasionally, no splits are observed after amyloid deposition; amyloid bodies below lamina densa cause the disruption at the level of the lamida lucida. 8 Ochiai et al 9 observed keratinocyte protrusions penetrating the basal membrane and surrounding the amyloid below the lamina densa.…”
Section: Discussionmentioning
confidence: 98%